Technical success and associated economic implications of conventional re-entry devices in subintimal recanalization of femoro-popliteal chronic total occlusions - Katharina Rippel; Hannes Ruhnke; Bertram Jehs; Thomas Kroencke; Christian Scheurig-Muenkler (Diagnostic and Interventional Radiology, 2023)

(untitled)
PURPOSERe-entry devices contribute to the high success rate of subintimal recanalization of chronic total occlusions (CTO). However, to date, there are no studies comparing the available conventional re-entry devices concerning the impact of their technical success on economic aspects, as these devices differ greatly in their acquisition costs. This prospective observational study intends to contribute to this question.METHODSPrior to the start of the prospective study, all previous applications of the Outback® in femoro-popliteal CTO since its introduction to our hospital were analyzed retrospectively (n = 31). From June 2018 until January 2020, all patients with femoro-popliteal CTO treated with clear subintimal recanalization were included (n = 109). In the case of failed spontaneous re-entry, either the OffRoad® (study arm I, n = 20) or the Enteer® catheter (study arm II, n = 20) was used. If assisted re-entry failed, the Outback® device was used as a bailout. Baseline demographic and clinical data, morphologic characteristics, and technical success were documented. Additional per-patient costs due to the use of re-entry devices were analyzed.RESULTSA retrospective evaluation of all Outback® applications revealed a technical success rate of 97% (30/31). In the prospective study, 63% (68/109) were successfully treated without using re-entry devices. The overall procedural success was 95% (103/109). In study arm I, the OffRoad® achieved a success rate of 45% (9/20), with a subsequent successful application of the Outback® in 80% (8/10) of the failed cases. In study arm II, the Enteer® was successfully employed in 60% (12/20) of cases, and the Outback® was then used successfully in a further 62% (5/8) of cases. Too large a distance between the device and the target lumen was a knockout criterion for all tested devices, leading to a subgroup analysis with the exclusion of three cases, resulting in a success rate of 47% for the OffRoad® and 67% for the Enteer® device. Furthermore, in severe calcification, only the Outback® reliably enabled revascularization. Significant savings of almost €600 were only achieved in study arm II according to German prices.CONCLUSIONWith proper patient selection, a gradual approach with the Enteer® as the primarily used device, with the Outback® used additionally in case of failure, leads to significant savings and can be recommended. In severe calcification, the Outback® should be used as the primary device.